Play, a Pedagogical Strategy that Favours the Learning of Mathematics (Quaestiones Disputatae: temas en debate, 2021)
The article refers to the research developed with second grade students of the Instituto Tecnológico Salesiano Eloy Valenzuela (ITS), Sede C of Bucaramangaabout the learning of mathematics. The study falls within the paradigm of qualitative research; the process of enquiry is inductive, and the strategy selectedto intrpret the findings is descriptive. In the development of the research, the action-research methodology proposed by Kemmis, S. and McTaggart, R. (1998),cited by Latorre (2005), was applied. From this perspective, the research follows a cyclical process that occurs as a spiral in four phases: planning, action, observation and reflection.Based on the performance in the diagnostic test, the Classroom Pedagogical Project: Learning and Playing with Mathematics was implemented through tendidactic sequences (Díaz, 2013) with play as an active and creative support for learning. As a result of the pedagogical intervention, students showed satisfactory performance in the final test; a change in attitude, greater commitment, synergy in teamwork and respect for individual roles and the rules established in each of the games were observed.
Keywords: Educational strategy, game, mathematics, project, learning